Ignoring the sacroiliac joint in chronic low back pain is costly - Polly DW; Cher D (Dove Medical Press, 2016)
David W Polly,1,2 Daniel Cher3 1Department of Orthopedic Surgery, 2Department of Neurosurgery, University of Minnesota, Minneapolis, MN, 3SI-BONE, Inc., San Jose, CA, USA Background: Increasing evidence supports minimally invasive sacroiliac joint (SIJ) fusion as a safe and effective treatment for SIJ dysfunction. Failure to include the SIJ in the diagnostic evaluation of low back pain could result in unnecessary health care expenses. Design: Decision analytic cost model. Methods: A decision analytic model calculating 2-year direct health care costs in patients with chronic low back pain considering lumbar fusion surgery was used. Results: The strategy of including the SIJ in the preoperative diagnostic workup of chronic low back pain saves an expected US$3,100 per patient over 2 years. Cost savings were robust to reasonable ranges for costs and probabilities, such as the probability of diagnosis and the probability of successful surgical treatment. Conclusion: Including the SIJ as part of the diagnostic strategy in preoperative patients with chronic low back pain is likely to be cost saving in the short term. Keywords: chronic low back pain, lumbar fusion, sacroiliac joint pain, sacroiliac joint fusion, healthcare costs, decision modeling